The Immunomodulatory Potential of Wharton's Jelly Mesenchymal Stem/Stromal Cells - Fernanda Vieira Paladino; Juliana de Moraes Rodrigues; Aline da Silva; Anna Carla Goldberg (Hindawi Limited, 2019)
The benefits attributed to mesenchymal stem/stromal cells (MSC) in cell therapy applications are mainly attributed to the secretion of factors, which exhibit immunomodulatory and anti-inflammatory effects and stimulate angiogenesis. Despite the desirable features such as high proliferation levels, multipotency, and immune response regulation, there are important variables that must be considered. Although presenting similar morphological aspects, MSC collected from different tissues can form heterogeneous cellular populations and, therefore, manifest functional differences. Thus, the source of MSC should be a factor to be considered in the development of novel therapies. The following text presents an updated review of recent research outcomes related to Wharton's jelly mesenchymal stem/stromal cells (WJ-MSC), harvested from umbilical cords and considered novel and potential candidates for the development of cell-based approaches. This text highlights information on how WJ-MSC affect immune responses in comparison with other sources of MSC.